Human resource management practices in Nepalese organizations: Some observations - Shrestha, Prakash (NCC Journal, 2022)
HRM practices aim to increase employee effectiveness in an organization. They care about the organization's people resources and work to grow and maintain their top-notch initiatives in a challenging and constantly shifting environment. That is why organizations need to concentrate on effective HRM practices. With this regard, this paper aims to explore some observations of HRM practices in Nepalese organizations using desk research, specific real-world examples, and various studies. It considers corporate planning and objectives, human resource planning, recruitment, selection and placement, training and development, performance management, pay and benefits, job design, and employee relations as the key HRM practices that are employed in the context of Nepal.